Emotive facets of place meet urban analytics - Acedo, Albert (2022)
Acedo, A., González‐pérez, A., Granell, C., & Casteleyn, S. (2022). Emotive facets of place meet urban analytics. Transactions in GIS, 26(7), 2954-2974. https://doi.org/10.1111/tgis.12990 ----- Funding: Albert Acedo Sánchez is funded by the Juan de la Cierva–Formación Programme of the Spanish government, Grant No. FJC2019-039230-I, the Fundação para a Ciência e a Tecnologia (FCT), Grant No. 2021.00086.CEECIND, and the European Union (NextGenerationEU) through the Spanish Ministry of Universities grants Maria Zambrano (Grant No. MZ-697591) Alberto González-Pérez is funded by the Spanish Ministry of Universities, Grants No. FPU17/03832. This study was supported by the projects GACUJI/2021/08 funded by the Universitat Jaume I, Spain, and PID2020-120250RB-100 (SyMptOMS-ET) funded by the Spanish government, Grant No. MCIN/AEI/10.13039/501100011033.